TREATMENT OLI TRAFO TERHADAP PENINGKATAN TEGANGAN TEMBUS PADA TRAFO DISTRIBUSI KA 756 DI BY PASS NGURAH RAI - Abasana, I Gusti Ketut; Teresna, I Wayan (BULETIN FISIKA; Vol 14 No 2 (2013): BULETIN FISIKA, 2013)
The transformer is an electrical apparatus that is included in the classification of static electricity machine and serves to channel the energy / power from high voltage to low voltage or vice versa, with the same frequency. Transformer oil, according to the standard test PLN (SPLN) 49-1/1992 method IEC 158 and 296 shall have a minimum insulation resistance of 30 kV / 2.5 mm. This causes the decrease in insulation resistance not optimal power is supplied to the customer. Also can cause fatal damage to the transformer itself as the occurrence of a short circuit causing the transformer to explode. Therefore, to maintain performance or life time of the transformer itself needs to be treated at least once a year. Men-oil treatment is that efforts should be made to ensure that prisoners are permitted insulation standards and transformer can operate optimally.